Comparison of digestibility between different cultivar of banana (Musa sapientum) peels using an in vitro gas production method - Suhaimi, Mohd Erfan Haqique (2017)
Feed is the most important component of livestock production and it accounts up to 70 per cent of the total cost of maintenance. The increasing prices of animal feed supplements are one of the challenges facing the livestock industries all around the world. The unorthodox feed stuff used to reduce the grass and concentrate are, by using waste product as an option. The aim of this study is to measure the digestibility of banana (Musa sapientum) peels from different cultivar as a supplementation on top of Napier grass (Pennisetum purpureum) as basal feed. Gas production via in vitro gas production technique and in vitro dry matter digestibility (IVDMD) post incubation period were analysed to observe the digestibility pattern between treatments. N consist of (100% Napier grass + 0% banana peel; n=6) followed by NS consist of (85% Napier grass + 15% Saba peel; n=6), NP consist of (85% Napier grass + 15% Plantain peel; n=6), and NSP consist of (85% Napier grass + 7.5% Saba peel + 7.5% Plantain peel; n=6). There were significant (p<0.05) differences between Saba peel and plantain peel in term of chemical composition. The crude protein of the peels ranged from 6.61% to 7.95% of dry matter (DM); acid detergent fibre from 26.20% to 34.48% DM and acid detergent lignin ranged 26.97% to 92.30% DM; neutral detergent fibre ranged from 46.11% to 49.06% DM. Total gas production after 72 h incubation ranged between 20 mL and 25 mL/0.2 g of substrate. At 4 and 8 h of incubation, the gas production were significantly (p<0.05) different between NS and NP in which, NS produced higher gas volume at this hour compared NP. In in vitro dry matter digestibility (IVDMD), NS shows the highest IVDMD percentage which was 12.77%, indicate it has higher digestibility compared to other treatment. There was no correlation between parameter of gas production and IVDMD percentage due some errors during conducting the experiment. In conclusion, banana peels from different cultivars have no different rate of digestibility but NS shows higher gas production rate than NP.